Efficiency of Different Dose of Zinc on Growth, Productivity and Economic Returns of Mustard in AEZ 11 of Bangladesh (Journal of Environmental Science and Natural Resources, 2015)
An experiment was carried out in the farmers field at the MLT site Tularampur, Narail (AEZ-11) during the rabi season of 2011-12 to evaluate the performance of newly released mustard varieties to Zn fertilization. Three levels of zinc 2, 3 and 4 kg/ha from zinc sulphate was used in BARI Sharisha-14. The experiment was carried out in a tree with 6 dispersed replications. Response of mustard to zinc fertilizer was significantly evident for yield. The highest yield (1.42 t/ha) was obtained from T1(3 kg Zn/ha) which was statistically higher than T2 (4 kg Zn/ha) yielding 1.37 t/ha. Both the treatments gave higher yields over the control. From the economic analysis, the highest gross margin was observed (Tk. 47695/ha and Tk. 44595/ha) and highest benefit cost ratio (BCR) (1.57 and 1.45) obtained from T2 treatment followed by T3 treatment, respectively.DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22037 J. Environ. Sci. & Natural Resources, 6(1): 37-40 2013